Lactic acidosis: implications for human exercise performance - Cairns, S. P.; Lindinger, M. I. (European Journal of Applied Physiology, 2025)
During high-intensity exercise a lactic-acidosis occurs with raised myoplasmic and plasma concentrations of lactate- and protons ([lactate-], [H+] or pH). We critically evaluate whether this causes/contributes to fatigue during human exercise. Increases of [lactate-] per se (to 25 mM in plasma, 50 mM intracellularly) exert little detrimental effect on muscle performance while ingestion/infusion of lactate- can be ergogenic. An exercise-induced intracellular acidosis at the whole-muscle level (pHi falls from 7.1-7.0 to 6.9-6.3), incorporates small changes in slow-twitch fibres (pHi ~ 6.9) and large changes in fast-twitch fibres (pHi ~ 6.2). The relationship between peak force/power and acidosis during fatiguing contractions varies across exercise regimes implying that acidosis is not the sole cause of fatigue. Concomitant changes of other putative fatigue factors include phosphate metabolites, glycogen, ions and reactive oxygen species. Acidosis to pHi 6.7-6.6 at physiological temperatures (during recovery from exercise or induced in non-fatigued muscle), has minimal effect on force/power. Acidosis to pHi ~ 6.5-6.2 per se reduces maximum force (~12%), slows shortening velocity (~5%), and lowers peak power (~22%) in non-fatigued muscles/individuals. A pre-exercise induced-acidosis with ammonium chloride impairs exercise performance in humans and accelerates the decline of force/power (15-40% initial) in animal muscles stimulated repeatedly in situ. Raised [H+]i and diprotonated inorganic phosphate ([H2PO4-]i) act on myofilament proteins to reduce maximum cross-bridge activity, Ca2+-sensitivity, and myosin ATPase activity. Acidosis/[lactate-]o attenuates detrimental effects of large K+-disturbances on action potentials and force in non-fatigued muscle. We propose that depressive effects of acidosis and [H2PO4-]i on myofilament function dominate over the protective effects of acidosis/lactate- on action potentials during fatigue. Raised extracellular [H+]/[lactate-] do not usually cause central fatigue but do contribute to elevated perceived exertion and fatigue sensations by activating group III/IV muscle afferents. Modulation of H+/lactate- regulation (via extracellular H+-buffers, monocarboxylate transporters, carbonic anhydrase, carnosine) supports a role for intracellular acidosis in fatigue. In conclusion, current evidence advocates that severe acidosis in fast-twitch fibres can contribute to force/power fatigue during intense human exercise.